Integrals of products of Bessel functions for applied electrodynamic problems - Pochernyaev, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We determine definite integrals of products of Bessel functions of the first and second kind of different orders with various complicated arguments with finite limits of integration.